COMMUNICATION OF ISLAMIC CIVIC ORGANIZATION IN OVERCOMING THE CONFLICT AND IMAGING AT NORTH SUMATERA (ANALYSIS OF MUHAMMADIYAH) - Hasnun Jauhari Ritonga; Syukur Kholil Kholil; Yusnadi Yusnadi Yusnadi (State Islamic University of North Sumatra Indonesia, 2017)
Organizational communication is part of an effort to minimize conflict within the organization. Conducive organizational climate one of them is influenced by the effectiveness of organizational communication. This study aims to show that organizational communication becomes very important in the life of the organization. The research results show that The nature of coordination is the realization of a cooperation, mutual respect or appreciation of duties and functions and responsibilities due to the principle of the division of tasks, functionalization and consequence of a range or level of control, in which the leader must foster, guide, direct and control various activities in a large and complex organization, where various functions and activities must be performed by various units of work (units) that must be done in an integrated and simultaneous manner. Taking into account the existence of Muhammadiyah North Sumatra as part of a large organization in Indonesia, in principle coordination of tasks running vertically, horizontally, and functionally. Vertical coordination is carried out in order to harmonious and synchronous cooperation harmonization from higher-level institutions to other institutions of lower degree. Horizontal coordination is done in order to harmonious and synchronous cooperation between institutions or equivalent units. While functional coordination is done in order to harmonious harmonious and synchronous cooperation between institutions that have similarities in job functions such as among fellow heads of public relations